Elevating Demand: Product Quality and Purchase Intention in Balinese Silver Craft Economies - Tjokorda Gde Agung Wijaya Kesuma Suryawan; Ni Komang Lilis Tri Paramita; Cokorda Istri Agung Vera Nindia Putri; I Komang Putra (Warmadewa Economic Development Journal (WEDJ), 2025)
This quantitative investigation provides a nuanced examination of product quality’s impact on purchase decisions, with purchase intention as a key behavioural mediator. The study focuses on consumers of Yas Silver in Gianyar, Bali, a culturally rich, tourism-dependent context vital to economic development. Employing a descriptive-associative approach, data were meticulously collected via Likert-scale surveys from 96 respondents, purposively and randomly sampled from an unstated population. The findings revealed statistically significant positive effects: product quality significantly enhances purchase intention and directly drives purchase decisions; purchase intention significantly mediates this relationship. Contributing to international marketing, behavioural economics, and economic development literature, this research empirically substantiates the crucial role of product quality, operating through purchase intention, in shaping consumer behaviour within similar tourism-reliant economies. The findings offer pertinent, behaviourally informed, and strategically actionable marketing insights for international businesses, particularly in artisanal and tourism sectors, seeking to optimise marketing effectiveness and foster sustainable economic growth in global cultural destinations.